Use of microdoses for induction of buprenorphine treatment with overlapping full opioid agonist use: the “Bernese method” - Hämmig R; Kemter A; Strasser J; von Bardeleben U; Gugger B; Walter M; Dürsteler KM; Vogel M (Dove Medical Press, 2016)
Robert Hämmig,1 Antje Kemter,2 Johannes Strasser,2 Ulrich von Bardeleben,1 Barbara Gugger,1 Marc Walter,2 Kenneth M Dürsteler,2 Marc Vogel2 1Division of Addiction, University Psychiatric Services Bern, Bern, Switzerland; 2Division of Substance Use and Addictive Disorders, University of Basel Psychiatric Hospital, Basel, Switzerland Background: Buprenorphine is a partial µ-opioid receptor agonist used for maintenance treatment of opioid dependence. Because of the partial agonism and high receptor affinity, it may precipitate withdrawal symptoms during induction in persons on full µ-opioid receptor agonists. Therefore, current guidelines and drug labels recommend leaving a sufficient time period since the last full agonist use, waiting for clear and objective withdrawal symptoms, and reducing pre-existing full agonist therapies before administering buprenorphine. However, even with these precautions, for many patients the induction of buprenorphine is a difficult experience, due to withdrawal symptoms. Furthermore, tapering of the full agonist bears the risk of relapse to illicit opioid use.Cases: We present two cases of successful initiation of buprenorphine treatment with the Bernese method, ie, gradual induction overlapping with full agonist use. The first patient began buprenorphine with overlapping street heroin use after repeatedly experiencing relapse, withdrawal, and trauma reactivation symptoms during conventional induction. The second patient was maintained on high doses of diacetylmorphine (ie, pharmaceutical heroin) and methadone during induction. Both patients tolerated the induction procedure well and reported only mild withdrawal symptoms.Discussion: Overlapping induction of buprenorphine maintenance treatment with full µ-opioid receptor agonist use is feasible and may be associated with better tolerability and acceptability in some patients compared to the conventional method of induction. Keywords: subutex, suboxone, heroin, opiate, substitution